Aplikasi Diagnosis Karies pada Gigi Manusia Berbasis Web - Silvia Silvia; Christine Leonita; Virginia Virginia; Yosua Jaya Candra; Nina Sevani (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
Dental caries is the dental health problems that are often neglected by humans. If the dental caries is neglected, it can lead to the risk of death. Web-based application to diagnose dental caries of human, aims to help public to do early diagnose of the presence of human dental caries. The benefit of this web-based application is to give suggestion for the user and assist them for the further handling. There are three kinds of human carries that can be detected by this application. The diagnose process started with some questions to be answered by the user. The answers will be compared with rules in the system to make conclusion. This application has been tested and evaluated using black-box and white-box testing method. The results of the tests and evaluation stated that this application can function properly to make early diagnose of human caries.